From Teaching Experience to Reflective Practice: The Role of Teaching Portfolios in Faculty Development in Medical Education - Yoana Priska; Monica Chandra (Jurnal Multidisiplin Indonesia, 2026)
Medical educators are expected to demonstrate pedagogical competence alongside clinical expertise. Teaching portfolios have been proposed to promote reflective practice and continuous professional development, but their educational role has not been comprehensively synthesised. Objective: This narrative review synthesised current evidence on the role of teaching portfolios in supporting reflective practice and faculty development in medical education. Methods: A literature search was conducted in Google Scholar, PubMed, and ERIC for articles published between 2015 and 2025. Relevant articles were identified through title and abstract screening, followed by full-text review. A total of 32 eligible studies were included and analysed using a thematic synthesis approach. Studies were included if they discussed teaching portfolios in medical education contexts in relation to reflective practice, faculty development, or feedback. Articles focusing solely on student learning portfolios, opinion pieces without empirical evidence, and studies not relevant to medical educators were excluded. Results: Teaching portfolios were consistently identified as tools that encourage structured reflection rather than simply documenting teaching activities. Their educational value is strengthened when combined with multisource feedback and mentoring, supporting continuous professional learning and the development of educators' professional identity. However, successful implementation depends on institutional support, a constructive feedback culture, and longitudinal faculty development. Conclusion: Teaching portfolios are most effective when embedded within supportive faculty development programmes that promote reflection, feedback, and continuous learning, enabling educators to transform teaching experience into meaningful professional growth.